“For He has Saved Daniel from the Power of the Lions”: The Book of Daniel’s Queer and Trans/gressive Spirituality - Fagnant, Nick (Lumen et Vita, 2024)
This essay proposes that the Hebrew Scriptures’ “Book of Daniel” offers powerful spiritual resources for Queer and trans* folk in the contemporary world. First, this essay describes the four strands of Queer theology offered by Rev. Dr. Patrick Cheng. Second, this essay employs these strands as a liberatory hermeneutic to analyze Daniel’s transgressive text, ambiguous characters, folk stories, apocalyptic visions, and unifying theme. In doing so, this essay interrogates Daniel’s multivalent spirituality that resists empire while trusting in God. Finally, this essay suggests that Daniel reveals an embodied spirituality of resistance-and-faith for present-day Queer and trans* folk to unmask and resist necropolitical hegemony in ways that deepen hope and trust in God’s justice and coming reign.